User-Friendly Interface and Comprehensive Features for Hostel Management - Helini Kolan; Keerthana Mungi; Lekhana Somayajula; Harshitha Achanta; Vaishnavi Edulakanti; Haryanto Haryanto (CV Media Inti Teknologi, 2025)
Background of study: Hostel administration in academic institutions has traditionally relied on manual processes such as paper-based record keeping, in-person registration, and ad-hoc maintenance communication. These fragmented practices often lead to inefficiencies, delays, miscommunication, and data inaccuracy. As student populations grow and operational demands increase, institutions require modernized systems that integrate automation, usability, and real-time information management to improve service delivery and resource allocation. However, existing solutions frequently lack comprehensive features, scalability, or user-centric design, indicating a clear gap in the availability of accessible and robust digital hostel management platforms.Aims: This study aims to design and implement a user-friendly, web-based Hostel Management System (HMS) that consolidates key administrative operations including student registration, room allocation, maintenance reporting, and occupancy tracking within a unified interface. The scope encompasses database design, workflow automation, interface usability, security provisions, and system evaluation through functional demonstrations.Methods: The system was developed following an Agile methodology, enabling iterative refinement based on user feedback. Dataset acquisition involved collecting student, room, facility, and maintenance information, followed by preprocessing steps such as data cleaning, normalization, and categorization to ensure accuracy. The architecture employed modular design principles, a web-based interface for multi-device accessibility, and security measures such as encrypted storage and role-based access control. Functional testing, integration testing, and user acceptance trials validated system performance and reliability.Result: The implemented HMS successfully automated core hostel processes improved real-time data access, and significantly reduced manual workload for administrative staff. Features such as automated room allocation, maintenance request tracking, virtual hostel viewing, and dashboard-based monitoring demonstrated high usability and operational effectiveness. User feedback indicated enhanced transparency, faster response times, and improved overall efficiency in hostel management.Conclusion: The proposed system provides a scalable, secure, and intuitive solution that modernizes hostel operations. By integrating comprehensive features within a user-friendly platform, the HMS enhances administrative productivity and student satisfaction. Its modular architecture and cloud-ready design position it for future enhancements, including AI-driven analytics, mobile integration, and predictive resource planning.